HIV/AIDS SEBAGAI “RUANG” PELAYANAN PASTORAL GEREJA - Robinson Simanungkalit (Jurnal Christian Humaniora, 2019)
It is important to explain some important things on Human Immunodeficiency Virus (HIV) or Acquired Immunodeficiency Syndrome (AIDS). This study was aimed to to provide a proper understanding on the HIV/AIDS. Consequently, this study described what the HIV/AIDS is, the history of the emergence of HIV/AIDS, the transmission of HIV/AIDS, and the effects of HIV/AIDS on infected human. People infected with HIV and AIDS are referred to as PLWHA (People living with HIV and AIDS). They may be church citizens. Therefore, the church must not "turn a blind eye", but is required to be proactive in responding to people who have infected with HIV/AIDS.BAHASA INDONESIA ABSTRACT: Sangatlah penting untuk menjelaskan beberapa hal penting tentang HIV/AIDS guna memberikan pemahaman yang benar tentang HIV/AIDS. Dibutuhkan penjelasan tentang apa itu HIV/AIDS, Sejarah munculnya HIV/AIDS, Penularan HIV/AIDS dan dampak yang ditimbulkan oleh HIV/AIDS terhadap orang- orang yang terinfeksi. Orang yang terinfeksi HIV dan AIDS itu disebut sebagai ODHA (Orang yang hidup dengan HIV dan AIDS). Mungkin saja mereka adalah warga gereja dan karena itu gereja tidak boleh “menutup mata” tetapi dituntut untuk proaktif dalam menyikapi keberadaan warganya yang terinfeksi HIV/AIDS.Keywords: HIV/AIDS, ODHA